Sobrecarga laboral al personal de salud que trabaja en el área de emergencias del Hospital Básico Baños, durante la pandemia de COVID-19 en el año 2020. - Cordero Carrasco, Juver Paul (2023)
This Research Project is proposed based on a clear violation of Ecuadorian labor regulations, clearly caused by the work overload of health personnel of the different Hospitals in the country as a result of the emergence of the Covid-19 pandemic in March 2020; this overload directly affects the doctors and nurses who worked in the country's health homes during the pandemic, seeing their rights as workers violated and, at the same time, violating the legal regulations in force in Ecuador that protects workers public and/or private workers. The main antecedent that must be taken into account is the emergence of the pandemic at the hands of Covid-19, and the effects that these produced in society; this aforementioned Covid-19 is nothing more than an infectious disease caused by the SARS-CoV-2 virus, which affected the health of all people, causing a massive number of infected, who were treated on the front line by doctors and nurses from the different health homes in the country, where it was possible to see that they worked at their maximum capacity to care for patients, as a result of which, even the health personnel were forced to work more hours than their daily shifts. The country had its first confirmed case of Covid-19 on February 29, 2020, with which a massive wave of infections was unleashed at the national level, therefore, it was a matter of weeks for the corresponding measures to be taken, such as mandatory quarantine throughout Ecuador, as well as the curfew in the afternoon and at night, in order to reduce the number of daily infections suffered by all the provinces of the country, mainly in the Costa region. This project is mainly justified by the need to identify how the work overload of health personnel is configured in a violation of the rights of the worker and Ecuadorian regulations. To reach our objective, a qualitative and quantitative research will be used 4 as a methodology since interviews and surveys will be applied to health personnel who work in the Emergency area of the Baños Basic Hospital, this being the population and sample applied to the project; In addition, based on the aforementioned, the type of research applied to this project is qualitative and quantitative research, taking into account the type of data that will be obtained through the research. Finally, within this Project it is expected to identify the way in which the work overload of health personnel who work in the Emergency area of the Basic Baths Hospital is configured as a violation of what is determined by our current labor regulations in the country, with what which is expected to meet the objectives, general and specific, raised in this research.